High-load strength training compared with standard care treatment in young adults with joint hypermobility and knee pain: study protocol for a randomised controlled trial (the HIPEr-Knee study) - Birgit Juul-Kristensen; Jonas Bloch Thorlund; Peter Henriksen; Behnam Liaghat; Jens Bojsen-Møller; Afsaneh Mohammadnejad; Bibi Dige Heiberg (BMJ Open)
Introduction Patients with generalised joint hypermobility, including knee hypermobility (GJHk), often experience knee pain and are typically managed with low-intensity strength training and/or proprioceptive training as part of standard care. However, not all patients experience satisfactory outcomes. High-load strength training may offer additional benefits, such as increased muscle cross-sectional area, neural drive and tendon stiffness, which may reduce pain and improve active knee joint stability during movement tasks and daily activities. So far, no randomised controlled trials (RCTs) have compared high-load strength training with traditional treatment strategies (standard care) for this patient group.Methods and analysis In this RCT, we aim to recruit patients with GJHk and knee pain from primary care physiotherapy clinics in the Region of Southern Denmark and via social media. Patients with competing injuries or experience with high-load strength training will be excluded. Patients will be randomised (1:1 ratio) to either 2 weekly sessions of high-load strength training or standard care for 12 weeks. The primary outcome is self-reported knee pain during an activity nominated by the patient as the most aggravating for their present knee pain measured using the Visual Analogue Scale for Nominated Activity (VASNA, 0–100; 0=no pain and 100=worst imaginable pain). This will be collected at baseline, 6 weeks, 12 weeks and 12 months. Secondary outcomes include self-reported knee function and adverse events (collected at baseline, 12 weeks and 12 months), objective measurements including a 5-repetition maximum single-leg press, proprioception and single-leg-hop for distance (collected at baseline and 12 weeks), and a range of other outcome measures such as fear of movement, tendon stiffness and global perceived effect. We aim to recruit 90 patients in total to detect a 10 mm group difference in the primary outcome with 80% power.Ethics and dissemination This study was funded by Independent Research Fund Denmark (grant number 2034-00088B) on 14 June 2022; the Regional Committees on Health Research Ethics for Southern Denmark approved it (S-20230050) on 30 August 2023. The first recruitment site opened on 15 February 2024, and the final results will be submitted to a peer-reviewed journal to inform rehabilitation strategies for symptomatic GJHk.Protocol version 1, dated 4 July 2024.Trial registration number NCT06277401.